Difusi Inovasi Platform Kitabisa.Com Sebagai Media Baru Untuk Penggalangan Dana Secara Daring (Crowdfunding) - Sunjaya Sunjaya; Mulyani Pratiwi SW; Dera Alfiani (Jurnal Ilmiah Wahana Pendidikan, 2022)
Crowdfunding is a new technology which enables people to give a donation online or online. With the development of time and technology, crowdfunding is becoming a capable innovation bring closer the donor to the goal. It could reach many among one of them with to do digitization finance in activity fundraising or donation on the Kitabisa.com crowdfunding platform. In this paper, we study this use theory diffusion innovation as well as concepts regarding crowdfunding, problem social, and donation. As well as research this use paradigm constructive and approach qualitative, with to do analysis to the kitabisa.com platform.